2008
DOI: 10.1016/j.livsci.2007.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and inbreeding in the Greek Skyros horse

Abstract: Inbreeding and heterozygosity levels were calculated in a population of 77 horses of the endangered Skyros breed that had been raised since 1988 at an experimental farm. Twenty one horses were inbred with average inbreeding coefficient of 0.11 ( ± 0.02). Annual inbreeding change over the last 10 years was not significant (P N 0.05). Animals were genotyped for 18 microsatellite markers. Average number of alleles was 4.11 ( ± 0.43). Average theoretical and observed heterozygosity were 0.63 ( ± 0.06) and 0.66 ( ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 8 publications
4
6
0
Order By: Relevance
“…Based on the comparison of our results with inbreeding estimated for other horse breeds in the world, it can be stated that genetic diversity of both breeds in Poland is rather moderate. For example, mean inbreeding estimated for the Spanish Arab Horse was 7 % (Cervantes et al, 2008), which corresponds to our result for Polish primitive horse, whereas inbreeding reported for Greek Skyros and Lipizzan horses (Avdi and Banos, 2008;Curik et al, 2003) was higher (11 and 10.3 %, respectively) than observed in our study for Polish primitive horse and Hucul breeds. Interestingly, recent study by Pinheiro et al (2013) regarding genetic diversity of the Sorraia breed (which can be considered as an Iberian analogue of the Polish primitive horse) showed an extremely high values (26.99 %) of mean inbreeding.…”
Section: Resultssupporting
confidence: 86%
“…Based on the comparison of our results with inbreeding estimated for other horse breeds in the world, it can be stated that genetic diversity of both breeds in Poland is rather moderate. For example, mean inbreeding estimated for the Spanish Arab Horse was 7 % (Cervantes et al, 2008), which corresponds to our result for Polish primitive horse, whereas inbreeding reported for Greek Skyros and Lipizzan horses (Avdi and Banos, 2008;Curik et al, 2003) was higher (11 and 10.3 %, respectively) than observed in our study for Polish primitive horse and Hucul breeds. Interestingly, recent study by Pinheiro et al (2013) regarding genetic diversity of the Sorraia breed (which can be considered as an Iberian analogue of the Polish primitive horse) showed an extremely high values (26.99 %) of mean inbreeding.…”
Section: Resultssupporting
confidence: 86%
“…H O averaged 0.637 (ranging from 0.426 for LEX05 to 0.768 for UMO11) while H E had a mean of 0.875 (ranging from 0.782 for HTG07 to 0.921 for HMS07). This was higher than what was found by Bjornstad and Roed (2002) in the English Thoroughbred breed and by Luis et al (2007) for the Sorraia breed but was similar to the findings of Shahsavarani and Rahimi-Mianji (2010) for the Caspian horse and Avdi and Banos (2008) for the Greek Skyros breed. Several markers displayed a significant deficit of heterozygotes due to within-population inbreeding in both subspecies and in the combined analysis.…”
Section: Resultssupporting
confidence: 85%
“…Many other studies have reported inbreeding results in horse breeds and their analyses show that the mean coefficient of inbreeding differs for different breeds and within the same breed in different countries. The average coefficient of inbreeding observed in this population was similar to findings by Sairanen et al (2009) for Standardbred trotters, and by Avdi and Banos (2008) for the endangered Skyros breed, but it was slightly smaller than those reported by Vostrá-Vydrová et al (2016) in grey horses and in Black horses. Moreover, the average inbreeding values observed in some farms were higher than those found in some dog breeds (Ciampolini et al, 2013;Cecchi et al, 2018) that use commonly and notoriously inbreeding as a mating method.…”
Section: Discussionsupporting
confidence: 81%